Vancomycin Dosing in Healthy-Weight, Overweight, and Obese Pediatric Patients - Eiland, Lea S. (Pediatric Pharmacy Advocacy Group, 2014)
OBJECTIVES: With an increase in vancomycin resistance and the prevalence of obesity in children, alterations of vancomycin dosing regimens may be necessary to achieve target serum concentrations. The primary objective of this study was to describe initial vancomycin dosing with resulting serum concentrations in healthy-weight and overweight/obese children. Secondary objectives include comparing vancomycin dosing regimens of healthy-weight and overweight/obese patients that produced target trough serum concentrations and evaluating the likelihood of attaining target concentrations by patient characteristics. METHODS: This retrospective review evaluated healthy-weight and overweight/obese patients, aged 2 to 18 years, who had vancomycin trough serum concentrations obtained between 2005 and 2010. Vancomycin dosing, initial trough serum concentrations, pharmacokinetic parameters, and patient demographics were collected for analysis. Target trough serum concentrations were defined as 10 to 20 mg/L. RESULTS: The study included 98 patients (48 healthy weight, 50 overweight/obese) of which only 14 patients (14.2%, 6 healthy weight, 8 obese) reached a target trough serum concentration with empiric dosing. No difference was found between the mean daily dosing of vancomycin that produced target trough serum concentrations in healthy-weight or overweight/obese patients (53.63 mg/kg/day vs 51.6 mg/kg/day, respectively). Demographic or clinical characteristics were not found to be associated with the likelihood of target trough serum concentration attainment. CONCLUSIONS: Vancomycin dosing in healthy-weight and overweight/obese pediatric patients did not reach target trough serum concentrations most of the time. In obtaining initial target serum concentrations, no dosing difference was identified for overweight/obese patients compared with healthy-weight patients. Alternate dosing strategies, therapeutic monitoring, and clinical outcomes should continue to be evaluated in this population.